An Efficient Route to Branched Allylsilanes through Copper-Catalyzed Allene Hydrosilylation Using Readily Available Silanes - Liu, Xiao-Tao; Chen, Jun-Jia; Zhan, Zhuang-Ping (Synlett, 2022)
A CuCl-catalyzed hydrosilylation of allenes with PhSiH3 has been developed. It is the first example of using readily available cheap silane reagents to generate branched allylsilanes in copper-catalyzed allene hydrosilylation. This base-metal catalyst offered an atom-economical and efficient route to branched allylsilanes with excellent regioselectivity.
Keywords: copper; hydrosilylation; allenes; branched allylsilanes; regioselectivity